The University Council of Jamaica: The Contemporary Higher Education Landscape in Jamaica - The University Council of Jamaica (The University Council of Jamaica, 2020)
This paper highlights important features of the evolution of the Jamaican higher education sector.
The University Council of Jamaica (UCJ) is the national External Quality Assurance Agency (EQAA) for higher education in Jamaica. As its core business, the UCJ facilitates institutional registration and the review of institutions, programmes and short courses for accreditation and recognition. By its very nature, quality assurance represents a process of various forms of quality monitoring, evaluation and review to establish stakeholder confidence that an institution or higher education provision measures up to international educational standards. In fulfilment of its mission, the UCJ facilitates: 1. the development of a system capable of responding more effectively to the country’s changing human resource needs; and 2. greater articulation among institutions constituting the higher education system.
Keywords: Higher education; Jamaica